Input Shortages in Mixed Economies An Application to Indian Manufacturing Industries - Sahay, Ratna (International Monetary Fund, 1991)
Widespread shortages in key inputs are common in mixed economies of developing countries. These shortages appear to occur at the same time that relatively high rates of capacity underutilization in manufacturing industries are observed. This paper develops a simple model which explains the existence of excess capacity when there are quantitative restrictions on key inputs. This model is tested using data for manufacturing industries in India, and the results indicate that shortages in domestic rather than imported inputs imposed binding constraints on capacity utilization rates